Traditional, systematic, or scoping reviews: how to choose the type of literature review that is appropriate in each case? - Codina, Lluís (Infonomy, 2024)
Presentation of the main types of literature reviews and elements to decide which is most suitable in each case. Traditional or narrative reviews are de-scribed on one hand, and the differences between systematic reviews and scoping reviews are explained. Recommendations for the most appropriate use of each are proposed.